Predictive factors of school performance in SAEB assessments: influence of school management (Research, Society and Development, 2020)
The activities developed in the school environment, by the School Director, can contribute for the educational institution to reach different levels in terms of educational quality, and this differential can be the result of the level of experience of the Director. Thus, the objective of this article was to observe which factors referring to the activities of the School Directors could contribute to the performance of high school students, in the large scale assessments of SAEB in 2017. After data collection on the government websit , the tasks related to the selection and treatment of these data were carried out and soon after, the Educational Data Mining phase, which included the execution of the Decision Tree, Random Forest and Gradient Boosted Tree algorithms. The results found by the Data Mining phase indicated that for both Portuguese and Mathematics, the Time of Experience of the School Director, in the exercise of the function, can contribute for the high school students to obtain better performances in the SAEB evaluations, in addition to this factor, others such as postgraduate level, actions to control failures and the socioeconomic level of the school also contributed to the students' academic performance. A more detailed study of the factors influencing performance can contribute to the elaboration of projects, which involve public policies, and which promote improvements in the entire school environment, as well as in the performance of students.